Changes in Serum Creatinine Concentration and Acute Kidney Injury (AKI) Grade in Dogs Treated with Hydroxyethyl Starch 130/0.4 From 2013 to 2015. (21st January 2017) - Sigrist, N.E.; Kälin, N.; Dreyfus, A.
Abstract : Background: Hydroxyethyl starch (HES) solutions may cause acute kidney injury (AKI) in humans. Objective: To compare AKI grades in 94 dogs exposed and 90 dogs that were unexposed to 6% HES‐130/0.4. Animals: Dogs receiving 6% HES‐130/0.4 (HES cohort) or crystalloids (unexposed cohort) between 2013 and 2015. Methods: Historical cohort study. Diagnosis, total cumulative dose and total mL/kg of HES administered, time frame of HES administration and serum creatinine concentrations up to 90 days after initiation of HES treatment were retrospectively reviewed. The AKI grades were retrospectively determined by IRIS guidelines. Results: Exposed dogs received a median cumulative dose of 69.4 mL/kg (range, 2–429 mL/kg) HES over a median of 4 (range, 1–16) days, resulting in a median dose of 20.7 (range, 2–87) mL/kg/d. Although the cohorts differed in terms of age and diagnosis, AKI grades were not significantly different at the evaluated short‐ and long‐term time points. Results of ordinal logistic regression identified the number of days of HES administration as significantly associated with an increase in AKI grade within 10 days ( P = .038), whereas there was no significant association among HES exposure, HES mL/kg/d, and an increase in AKI grade. Conclusions and Clinical Importance: HES‐130/0.4‐treated dogs were not more prone to develop AKI than HES‐untreated, but the number of HES days was significantly associated with an increase in AKI grade within 10 days post‐HES administration. The time frame of HES treatment should be kept short. Prospective, randomized clinical trials are required to assess the effect of HES on renal function in dogs.